2010
DOI: 10.5230/jgc.2010.10.4.212
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Upper Third Gastric Cancer during a 21-Year Period (Single Center Analysis)

Abstract: PurposeThe aim of this study was to determine proportions of upper third gastric cancer (UTG) among all gastric cancers and analyze clinicopathological features of the disease.Materials and MethodsThe medical records of 12,300 patients who underwent gastric surgery between 1986 and 2006 at Seoul National University Hospital (SNUH) were retrospectively reviewed. Clinicopathological features of 1,260 patients with UTG and 9,929 patients with middle or lower third gastric cancer (MLG) were compared, and annual pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…Several studies included AGC patients as well as EGC that differed from our study population, which may affect the discrepant results from our study in terms of tumor differentiation and Lauren’s classification. A large-scale retrospective Korean study demonstrated that undifferentiated and diffuse type were significantly frequent in the upper third gastric cancer than the middle or distal gastric cancer, which reinforces our study results [37]. We considered that predominance of undifferentiated type, as well as frequent SM invasion, in proximal stomach might be another characteristics of biologic behavior of proximal EGC, because undifferentiated EGCs usually show aggressive histologic findings with deeper invasion depth even in case with relatively small tumor size [38].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies included AGC patients as well as EGC that differed from our study population, which may affect the discrepant results from our study in terms of tumor differentiation and Lauren’s classification. A large-scale retrospective Korean study demonstrated that undifferentiated and diffuse type were significantly frequent in the upper third gastric cancer than the middle or distal gastric cancer, which reinforces our study results [37]. We considered that predominance of undifferentiated type, as well as frequent SM invasion, in proximal stomach might be another characteristics of biologic behavior of proximal EGC, because undifferentiated EGCs usually show aggressive histologic findings with deeper invasion depth even in case with relatively small tumor size [38].…”
Section: Discussionsupporting
confidence: 91%
“…Tumors were deeper, with a higher rate of lymph node metastasis in the EGJA group which agrees with other groups. 27 In accordance with the higher proportion of advanced stage, a lower radical degree rate was also observed in the EGJA group. Because of the special locations of cardia and fundus of stomach, EGJA especially Siewert type III tumors were not easy to detect under endoscopy compared with distal lesions.…”
Section: Discussionmentioning
confidence: 62%
“…A previous study demonstrated that the prognosis of the patients treated by a total gastrectomy was poorer compared to those who were treated by distal gastrectomy [28]. Resection margin status has been reported to have prognostic value in previous studies comparing GC patients from the West and the East [29,30].…”
Section: Discussionmentioning
confidence: 99%